Generating Important Insights into the Spectrum and Outcomes of Acute Heart Failure Across the African Continent: The Sub-Saharan Africa Survey of Heart Failure (THESUS-HF II) - Karen Sliwa; Simon Stewart; Charle Viljoen; Shaazia Allie; Julia Hahnle; Albertino Damasceno; Neusa Jessen; Mahmoud Sani; George Nel; Duard Smith; Beth Davison; Gad Cotter (Global Heart)
Background: Heart failure (HF) affects approximately 64.3 million people worldwide. Despite notable progress over the past two decades in advancing the understanding of heart failure in Africa–a condition often more lethal than many cancers–important knowledge gaps persist. These include outdated data on access to care and a lack of information regarding the incidence, aetiology, availability, and affordability of HF medications. Objectives: To prospectively characterise the contemporary incidence, epidemiology, clinical presentation, and health outcomes of acute HF among a large, representative cohort of patients presenting to hospitals across diverse communities in Africa. Methods: The Sub-Saharan Africa Survey of Heart Failure (THESUS-HF II) is a pragmatic, multicentre, observational cohort study coordinated by the Pan-African Society of Cardiology (PASCAR). All 27 PASCAR member countries were invited to participate, along with over 5,000 clinicians from the PASCAR database. The survey comprises two components. First, a platform collecting data on each hospital’s catchment population, human resources, presence of specialised cardiology services, availability of diagnostic tools, and access to essential heart failure treatments. Second, a prospective observational study capturing all acute heart failure presentations to participating hospitals over seven weekdays within an 8-week period (from the start of surveillance). Data were collected on clinical characteristics and outcomes to discharge, 30 days, and six months. The study commenced in mid-2024 and includes approximately 50 hospitals across 16 countries spanning all major regions of the African continent. Conclusions: When completed, THESUS-HF II will be the largest and most comprehensive study of acute HF to date in Africa. It will provide invaluable insights into the contemporary characteristics and burden of acute HF in Africa, whilst indicating what is needed to improve health care planning and, ultimately, patient outcomes.